2018
DOI: 10.1590/0103-8478cr20180505
|View full text |Cite
|
Sign up to set email alerts
|

Levels of polychlorinated biphenyls (PCBs) in whole milk powderand estimated daily intake for a population of children

Abstract: Polychlorinated biphenyls (PCBs) are chemical contaminants classified as persistent organic pollutants. Although, their use has been banned for several decades, PCBs are still scattered in the environment and; therefore, all living organisms may be exposed to these compounds. Diet, especially fatty foods such as milk, has been recognized as one of the main sources of human exposure to PCBs. Hence, the aim of this study was to evaluate the residual levels of indicator PCBs in whole milk powder consumed by presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
4
3
Order By: Relevance
“…Costabeber et al . (2018) measured PCBs in milk powder samples and showed that the mean concentration of the total five PCBs was 0.230 ng/g fat, which was lower than the findings of this study.…”
Section: Resultscontrasting
confidence: 91%
“…Costabeber et al . (2018) measured PCBs in milk powder samples and showed that the mean concentration of the total five PCBs was 0.230 ng/g fat, which was lower than the findings of this study.…”
Section: Resultscontrasting
confidence: 91%
“…180 showed values below the limit of detection. The PCBs concentrations detected in this study were lower than those reported in other studies [60] , [61] , [62] . Findings from Japan have indicated that intake of PCB-contaminated foods is toxic to mothers [63] .…”
Section: Resultscontrasting
confidence: 93%
“…The results of six NDL-PCB levels in this research, in comparison with other researchers, concluded the contamination of environment (soil, air and water) with pesticides, contaminants from diesel trucks, products of petroleum, demolition of buildings and paints may cause pollution of livestock feed and agricultural products such as dairy products (Ahmadkhaniha et al 2017;Costabeber et al 2018). Furthermore, the proximity of animal farms to the oil refineries, industries and highways may cause livestock pollution, followed by contaminants in the dairy products.…”
Section: Evaluation Of 6 Ndl-pcbs In Cream and Ice-cream Samplessupporting
confidence: 56%
“…These contaminants reduce the activity of the thyroid gland (decreased serum levels of Triiodothyronine (T3) and Thyroxine (T4), weaken the immune system, decrease the levels of vitamin A in the liver; they also cause liver necrosis, fatty liver disease and liver hypertrophy, inhibition of the synthesis of neurotransmitters such as dopamine and interruption in brain function such as learning and memory, estrogenic and androgenic hormonal changes (Alharbi et al 2018;Cheney et al 2019;Elangovan et al 2019;Zhang et al 2021). The World Health Organization (WHO) and the International Agency for Research on Cancer (IARC) have classified PCBs as 2A, probable carcinogenic substances (Bayat et al 2011;Ahmadkhaniha et al 2017;Costabeber et al 2018).…”
Section: Introductionmentioning
confidence: 99%